2014
DOI: 10.5665/sleep.3308
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Aging and Restorative Processes: Subjective Sleep Quality and Duration Moderate the Association between Age and Telomere Length in a Sample of Middle-Aged and Older Adults

Abstract: The current study provides evidence for an association between sleep quality, sleep duration, and cellular aging. Among older adults, better subjective sleep quality was associated with the extent of cellular aging, suggesting that sleep duration and sleep quality may be added to a growing list of modifiable behaviors associated with the adverse effects of aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 49 publications
5
65
3
Order By: Relevance
“…Moreover, among those women for whom poor sleep quality was chronic, poorer sleep quality predicted shorter leukocyte telomere length. Additional work has extended these observations to older adults with assessment of sleep quality using a validated questionnaire (ie, Pittsburgh Sleep Quality Index, PSQI) and telomere length in peripheral blood mononuclear cells, and shown that age and self-reported sleep quality interact in predicting telomere length (Cribbet et al, 2014). Importantly, age was related to telomere length, and this association was more robust among poor sleepers.…”
Section: Sleep and Inflammaging: Experimental And Naturalistic Findingsmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, among those women for whom poor sleep quality was chronic, poorer sleep quality predicted shorter leukocyte telomere length. Additional work has extended these observations to older adults with assessment of sleep quality using a validated questionnaire (ie, Pittsburgh Sleep Quality Index, PSQI) and telomere length in peripheral blood mononuclear cells, and shown that age and self-reported sleep quality interact in predicting telomere length (Cribbet et al, 2014). Importantly, age was related to telomere length, and this association was more robust among poor sleepers.…”
Section: Sleep and Inflammaging: Experimental And Naturalistic Findingsmentioning
confidence: 94%
“…Importantly, age was related to telomere length, and this association was more robust among poor sleepers. Moreover, among older adults with good sleep quality, the association between age and telomere length was attenuated (Cribbet et al, 2014). further examined this question in older adults and evaluated differences in telomere in relation to diagnostic insomnia, and determined whether insomnia interacts with chronological age to increase cellular aging.…”
Section: Sleep and Inflammaging: Experimental And Naturalistic Findingsmentioning
confidence: 99%
“…In addition, the authors show us that prevalence of insufficient sleep in adults has been estimated at 20% and the effects on cognitive processing are increased the risk of human-error-related accidents and poses risks to safe operation in all modes of transportation and to performance in other safety-sensitive activities. Cribbet et al, (2014) add that sleep privation has been found to introduce an increase on circulating levels of inflammatory markers, because sleep-wake cycle is an important factor to development of the immune system and the changes via too. Edelman, Kudzma and Mandle (2014), show us that a person with difficulties with sleep may be tense and irritable, unable to tolerate stress and incapable of making health-promoting relationships.…”
Section: Sleep Disorders and Sleep Deprivationmentioning
confidence: 98%
“…It can reduce productivity and absenteeism; these are the most widely reported work performance impairments. Thus, Cribbet et al (2014), explain inadequate sleep is associated with adverse health consequences as likely susceptibility to the common cold, metabolic syndrome and type two diabetes. Another study, Stein and Pu (2012), found the sleep disorders can has impact on cardiac autonomic control (arrhythmogenesis), which led to morbidity and mortality, among people who has pre-existing heart disease and/or sleep disorders breathing.…”
Section: Sleep Disorders and Sleep Deprivationmentioning
confidence: 99%
“…Many studies have extensively examined shortened leukocyte telomere lengths (LTL), induced by cellular aging, as a risk factor for various age-related diseases [5][6][7][8][9]. However, few have examined the association between telomere lengths (TL) and sleep quality [10][11][12]. Previous studies have been limited by only examining the association of LTL with a subjective sleep quality measure, Pittsburgh Sleep Quality Index (PSQI) [13].…”
Section: Introductionmentioning
confidence: 99%